Type I primary neuropathic amyloidosis (Andrade, Portuguese): a clinical and laboratory study of 21 cases - Eduardo M. Azevedo; Milberto Scaff; Horacio M. Canelas; Antonio Spina-França (Arquivos de Neuro-Psiquiatria)
The authors present a review of 21 cases with the diagnosis of type I amyloid neuropathy based on epidemiological data, clinical evolution and histopathological findings. They call attention to the possibility of cranial nerves involvement (hyposmia, diplopia, masseterian hypotrophy, peripheral facial paralysis, hypoacusis, dysphonia, laryngeal paralysis, dysphagia, and trapezium muscle hypotrophy), to the severeness of the digestive symptoms, to the precocity of the autonomic disorders, and to the rather high incidence (6 cases) of heart involvement. The electromyography showed anterior horn involvement in 3 cases. The electrocardiography showed repolarization disorders in 11 cases, left ventricular overload in 6 cases and atrioventricular block in 5 cases. The serum proteins electrophoresis showed frequent abnormalities, but no typical curve could be obtained. The barium-contrasted X-rays of the gastrointestinal tract showed no anatomical lesions, but functional abnormalities (hypo or hypermotility) were found in 14 examinations. The Schilling test showed impairment of vitamin B12 absorption in 50% of the cases. However, with the concomitant administration of intrinsic factor (3 cases) there was improvement of its absorption. This proves that the gastric mucosa plays an important role in the disease malabsorption. The test with labeled-triolein showed slow absorption in 2 cases and steatorrhea in 3 (6 tests). For the confirmation of the amyloid deposits, the best histopathological procedure was nerve biopsy. In men, when the nerve biopsy was negative, testicular biopsy has shown to be a good option.